Sea ice rheology - Feltham, DL (ANNUAL REVIEWS, 2008)
The polar oceans of Earth are covered by sea ice. On timescales much greater than a day, the motion and deformation of the sea ice cover (i.e., its dynamics) are primarily determined by atmospheric and oceanic tractions on its upper and lower surfaces and by internal ice forces that arise within the ice cover owing to its deformation. This review discusses the relationship between the internal ice forces and the deformation of the ice cover, focusing on representations suitable for inclusion within global climate models. I first draw attention to theories that treat the sea ice cover as an isotropic continuum and then to the recent development of anisotropic models that deal with the presence of oriented weaknesses in the ice cover, known as leads.